MERDEKA (MEDIA PEMBELAJARAN DENGAN SAMPAH PLASTIK) UNTUK KELAS VI B DI UPT SPF SD INPRES BONTOMANAI - Nurjannah K; Klara Taruk Kambong; Nurul Hidayah Ilyas; Muh Ashar A Irsyad; Mutmainnah M; Nunu Alwiyah; Nur Hikmah; Miranda Astari; Putri Andani Irwan; Nur Wahyuni; Rahmatia Thahir; Munawwarah Thalib (STKIP Subang, 2024)
Learning media can originate from the utilization of plastic waste, which is an innovative step to enhance environmental awareness among students. This article outlines a community service activity conducted in Class VI B at UPT SPF SD Inpres Bontomanai, titled